Analisis Pengaruh Co-Firing Biomassa Terhadap Kinerja Peralatan Boiler PLTU Batubara Unit 1 PT. XYZ - Arifin, Miftahol (Journal of New Energies and Manufacturing, 2025)
To support policies related to the renewable energy mix, PLN has implemented a biomass co-firing program at power plants.It is not known how much it will affect the performance of boiler equipment, if the biomass co-firing is carried out continuously and at different generating load conditions. This study purpose to determine the impact of continuous biomass co-firing on the performance of boiler equipment at different generating load conditions. The method of data collection was carried out by observation and interview methods. For data analysis using calculations starting from finding the calculation value of specific fuel consumption and net plant heat rate is done manually using Microsoft Excel software, then the operating parameters of the boiler equipment performance are compared with standard or commissioning data. The co-firing process does not affect the performance of boiler equipment (Medium Speed Mill, boiler fan, Air Preheater) and all parameters of boiler equipment are still within limits. The performance of boiler equipment during the co-firing process is lighter, as can be seen from the Medium Speed Mill motor and boiler fan flows which decreased although not significantly. Despite changes in load, the performance of boiler equipment is still within limits and there is a decrease in the boiler furnace temperature. With co-firing, the average total production cost decreased from 485.324 Rp/Kwh to 484.585 Rp/Kwh. Meanwhile, the average Net Plant Heat Rate during the co-firing process during the study decreased from 2862.85 kcal/kwh to 2866.35 kcal/kwh